Sequential class switch recombination to IgE and allergen‐induced accumulation of IgE+ plasmablasts occur in the nasal mucosa of local allergic rhinitis patients - Testera‐Montes, Almudena; Palomares, Francisca; Jurado‐Escobar, Raquel; Fernandez‐Santamaria, Ruben; Ariza, Adriana; Verge, Jesus; Salas, Maria; Campo, Paloma; Mayorga, Cristobalina; Torres, Maria Jose; Rondon, Carmen; Eguiluz‐Gracia, Ibon (Allergy (Copenhagen), 2022)
Background The involvement of allergen‐specific (s)IgE in local allergic rhinitis (LAR) has been debated. Here, we investigate the effect of nasal allergen challenge with Dermatophagoides pteronyssinus (NAC‐DP) in mucosal and peripheral B‐cell subpopulations in LAR patients. Methods Nine LAR, 5 allergic rhinitis (AR), and 5 non‐atopic healthy control (HC) individuals were subjected to a 3‐day NAC‐DP protocol, and nasal biopsies and blood samples were collected before and after provocation. Nasal biopsies were used for immunohistochemistry and gene expression studies, whereas the frequency of lymphocyte subsets and basophil activation test (BAT) were analyzed in blood samples by flow cytometry. sIgG was measured in sera. Results NAC‐DP induced an increase in IgE+CD38+ plasmablasts in the nasal mucosa of LAR patients, but not in AR or HC individuals. Markers of sequential recombination to IgE (εCSR) (from IgG) were observed in 33% of LAR, 20% of AR, and 0% of HC subjects. NAC‐DP increased the proportion of peripheral CD19+CD20+CD38+ plasmablasts in AR and LAR patients, but not in HC. Expression of the mucosal homing receptor CXCR3 in peripheral CD19+CD20+CD38+ plasmablasts from LAR, AR, and HC individuals was 7%, 5%, and 0.5%, respectively. In vitro DP stimulation increased proliferating CD19+CD20+CD38+ plasmablasts in LAR and AR patients, but not in HC. Serum DP‐sIgG was higher in LAR and AR patients as compared to HC. BAT was positive in 33%, 100%, and 0% of LAR, AR, and HC subjects, respectively. Conclusion These results suggest that allergen exposure induces the sequential εCSR of IgG+CD19+CD20+CD38+ plasmablasts in the nasal mucosa of LAR patients. Allergen exposure induces the accumulation of IgE+ plasmablasts in the nasal mucosa of LAR patients. LAR patients display markers of sequential class switch recombination to IgE (IgM→IgG→IgE) in the nasal mucosa. LAR patients have allergen‐specific (s)IgE attached to the membrane of peripheral basophils and a higher level of serum sIgG than healthy individuals.Abbreviations: BAT, basophil activation test; εCSR, class switch recombination to IgE; CXCR, C‐X‐C motif chemokine receptors; NAC‐DP, nasal allergen challenge with Dermatophagoides pteronyssinus